A Stochastic Hybrid Blade Tip Timing Approach for the Identification and Classification of Turbomachine Blade Damage - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2018)
Dissertation (MEng)--University of Pretoria, 2017.